Profiles of free and bound phenolics extracted from Citrus fruits and their roles in biological systems: content, and antioxidant, anti-diabetic and anti-hypertensive properties. Issue 9 (14th August 2017) - Alu'datt, Muhammad H.; Rababah, Taha; Alhamad, Mohammad N.; Al-Mahasneh, Majdi A.; Ereifej, Khalil; Al-Karaki, Ghazi; Al-Duais, Mohammed; Andrade, Juan E.; Tranchant, Carole C.; Kubow, Stan; Ghozlan, Kawther A.
Abstract : Rutaceae plant extracts were investigated for their potential to inhibit hyperglycemia and hypertension related enzymes. Abstract : This study of selected plants of the Rutaceae family was carried out to investigate their phenolic content, antioxidant activity, and the in vitro inhibitory potential of extracted phenolics towards enzymes relevant for hyperglycemia and hypertension. The phenolic content, antioxidant activity and phenolic extract-mediated inhibitory activities for α-glucosidase and α-amylase were evaluated by spectrophotometry. The content of individual phenolics and the angiotensin I-converting enzyme (ACE) inhibitory activity of the phenolic extracts were evaluated by LC/MS-MS and RP-HPLC methods, respectively. A higher percentage of free phenolic content was seen for all the selected plants of the Rutaceae family (85.43–92.82% of the total phenolic content) than of the bound form (7.18–14.57% of total phenolic content). The major predominant bound phenolic in lemon and red blood orange was hesperidin. The major predominant bound phenolic in pummelo, shamouti and clementine was ferulic acid. The highest ACE and α-glucosidase inhibitory activity of the extracted phenolics from lemon was associated with free phenolic extracts obtained at 30 °C with values of 100% inhibition. Red blood orange free phenolic extract (30 °C) elicited the highest α-amylase inhibition activity (32.3%). In contrast, extracted bound phenolics after acid and base hydrolysis from all selected plants from the Citrus species were shown to induce activation of the ACE and α-amylase enzymes.